Adding a piece to the leaf epidermal cell shape puzzle - von Wangenheim, Daniel; Wells, Darren M.; Bennett, Malcolm J. (Elsevier, 2017)
The jigsaw puzzle-shaped pavement cells in the leaf epidermis collectively function as a load-bearing tissue that controls organ growth. In this issue of Developmental Cell, Majda et al. (2017) shed light on how the jigsaw shape can arise from localized variations in wall stiffness between adjacent epidermal cells.